Retrosigmoid Approach for Trapping and Removal of a Distal Dissecting Superior Cerebellar Artery Aneurysm in a Child - Ros de San Pedro, Javier (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives To demonstrate the feasibility of the retrosigmoid craniotomy for surgical management of vascular lesions located in the cerebellopontine angle (CPA).Method A previously healthy 2-year-old boy presented a sudden episode of torticollis to the left while sleeping. This episode was selflimited but it occurred two more times in a 6-day span. Torticollis worsened in the upright position, caused unsteady gait and refusal to walk from the child. The preoperative magnetic resonance imaging (MRI) showed the presence of a round, heterogenous vascular lesion in the left CPA. The lesion clearly enhanced after contrast administration. The preoperative angiography demonstrated the absence of left anterior inferior cerebellar artery anterior inferior cerebellar artery (AICA), being the left superior cerebellar artery (SCA) the supplier of the left lateral cerebellum. A blurred blush on the distal left SCA was compatible with a fusiform aneurysm. A standard retrosigmoid approach was planned for trapping and removal of the aneurysm.Results Through a left retrosigmoid craniotomy the aneurysm was approached, along with the different neurovascular structures of the CPA. The aneurysm leaned on the VII, VIII nerves complex and the superior petrosal vein, while tightly attached to the lateral cerebellum. Both proximal and distal SCA segments to the aneurysm were dissected, clipped, and divided for a complete trapping. Finally, the aneurysm was completely detached and removed in a whole piece. The patient fully recovered after surgery with no relapse of his symptoms.Conclusion The retrosigmoid craniotomy is a versatile approach that permits wide exposure of all CPA structures and adequate removal of distal aneurysms located in those cerebellar arteries supplying the lateral cerebellum.The link to the video can be found at: https://youtu.be/oEVfy4goFYM.
Keywords: cerebellopontine angle; dissecting aneurysm; distal superior cerebellar artery; aneurysm trapping; retrosigmoid craniotomy